2020
DOI: 10.1007/s00167-020-06059-5
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic reconstruction of the acromioclavicular joint provides the best functional outcomes in the treatment of chronic instability

Abstract: Purpose To systematically review the outcomes of surgical treatments of chronic acromioclavicular joint dislocation. Methods Studies were identified by electronic databases (Ovid, PubMed). All studies reporting functional and radiological outcomes of surgical treatments of chronic acromioclavicular joint dislocations were included. Following data were extracted: authors and year, study design, level of evidence, number of patients, age, classification of acromioclavicular joint dislocation, time to surgery, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 72 publications
(440 reference statements)
0
7
1
Order By: Relevance
“…However, reports that favored addition of an AC fixation due to superior clinical outcomes have also been published. 25 In our study, no statistically significant difference was observed in terms of clinical outcomes (ASES, CS, SSV, VAS) between the two surgical techniques.…”
Section: Discussioncontrasting
confidence: 56%
“…However, reports that favored addition of an AC fixation due to superior clinical outcomes have also been published. 25 In our study, no statistically significant difference was observed in terms of clinical outcomes (ASES, CS, SSV, VAS) between the two surgical techniques.…”
Section: Discussioncontrasting
confidence: 56%
“…Combined CC and AC ligament reconstruction showed better Constant and American Shoulder and Elbow Surgeons (ASES) scores compared to isolated CC ligament reconstruction. 48 However, conclusions were drawn based on studies with low levels of evidence. The systematic review by Borbas et al compared a non-biological fixation between the coracoid and clavicle, a biological reconstruction of the CC ligament, and ligament and/or tendon transfer.…”
Section: Resultsmentioning
confidence: 99%
“…It is in these patients that surgical treatment of chronic ACC dislocation is indicated. 6 , 7 , 20 , 21 …”
Section: Discussionmentioning
confidence: 99%